Heart Rate Variability and Baroreflex Sensitivity: Factors and Reference Ranges - Somboon, Paveena; Kulapatana, Surat; B. Watanapa, Wattana; Chattaris, Tanchanok; Sirivongrangson, Phatadon; Livikorn, Panomporn; Nonthadid, Thongchai; Hussarin, Poungpetch (Siriraj Medical Journal, 2023)
Objective: Heart rate variability (HRV) and baroreflex sensitivity (BRS) are influenced by various internal and external factors, making it necessary to establish universal reference values. We aimed to identify independent factors affecting short-term HRV parameters and BRS, as well as determine appropriate reference ranges, which are lacking in Asian populations. Materials and Methods: A total of 117 healthy Thai participants (aged 20-72 years; final n=117) were recruited based on strict criteria, including normal medical history, physical examination (ascertained by a physician), and normal blood profile. Spontaneous 5-minute HRV parameters (time and frequency domains) and spontaneous cross-correlation BRS were measured. Results: Age and resting heart rate (HR) are independently and inversely correlated with BRS and all HRV parameters, except LFnu (normalized low-frequency component) and LF/HF ratio (ratio of low- to high-frequency component). Sex differences were observed only in LF, which was higher in men. However, multiple regression analysis showed that sex did not significantly contribute as an independent variable to either HRV or BRS. Remarkably, BRS exhibited moderate to strong correlations with all HRV values, indicating its prominent role in influencing HRV and surpassing the impact of age. Conclusion: Age and resting HR were identified as independent factors influencing 5-minute HRV and BRS. Our findings suggest that decreased baroreflex function associated with aging may contribute to reduced HRV among the elderly. Furthermore, we established reference ranges for each 5-minute HRV parameter and BRS, categorized by age group (20-39, 40-59, and ≥60 years old). These reference values offer valuable clinical insights, particularly for Asian populations where such normative ranges were previously unavailable.